2007
DOI: 10.1093/jee/100.6.1880
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Transgenic Bacillus thuringiensis Corn Hybrids Against Cry1Ab-Susceptible and -Resistant Sugarcane Borer (Lepidoptera: Crambidae)

Abstract: A Louisiana strain of the sugarcane borer, Diatraea saccharalis (F.) (Lepidoptera: Crambidae), was selected for resistance to the CrylAb protein of Bacillus thuringiensis (Bt) by using an F2 screening procedure. Survival of Bt-resistant, -susceptible, and -heterozygous genotypes of sugarcane borer was evaluated on vegetative and reproductive stages of five non-Bt and seven Bt field corn, Zea mays L., hybrids in a greenhouse study. Larval survival was recorded 21 d after infestation of neonates on potted plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 0 publications
4
46
0
Order By: Relevance
“…Points are sample means and error bars show 1 SEM. An asterisk indicates a mean preference score that signiÞcantly differed from 0.5. sugarcane borer, Diatraea saccharalis (F.), on maize producing Cry1Ab, inheritance of resistance was not always recessive and depended on plant stage (Wu et al 2007, Crespo et al 2010. Comparisons across pest species indicate that recessive inheritance of resistance is one key factor in delaying the evolution of resistance (Tabashnik et al , 2009Carriè re et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Points are sample means and error bars show 1 SEM. An asterisk indicates a mean preference score that signiÞcantly differed from 0.5. sugarcane borer, Diatraea saccharalis (F.), on maize producing Cry1Ab, inheritance of resistance was not always recessive and depended on plant stage (Wu et al 2007, Crespo et al 2010. Comparisons across pest species indicate that recessive inheritance of resistance is one key factor in delaying the evolution of resistance (Tabashnik et al , 2009Carriè re et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a known Cry1Ab-resistant strain (Cry1Ab-RR-2004) of D. saccharalis was also included in the bioassays in this study to serve as a positive control. Cry1Ab-RR-2004 was established from a field collection in 2004, which has been well documented to be highly resistant to both Cry1Ab-maize plants and purified Cry1Ab protein (Huang et al, 2007a(Huang et al, , 2007bWu et al, 2007;Ghimire et al, 2011;Wangila et al, 2012). Individuals of the seven resistant strains were backcrossed 2-3 times with individuals from the Cry1Ab-SS strain and re-selected for Bt resistance using leaf tissue from Cry1Ab expressing maize plants during the F 2 generations of the backcross.…”
Section: Sources Of Cry1ab-susceptible and -Resistant Strains Of D Smentioning
confidence: 99%
“…Studies have shown that D. saccharalis is inherently less susceptible to Bt proteins than other major maize borer species such as European corn borer, Ostrinia nubilalis (Hübner), and southwestern corn borer, Diatraea grandiosella Dyar . Both Wu et al (2007) and Ghimire et al (2011) also reported that most commercial Cry1Ab maize hybrids did not express a ''high dose'' of Bt proteins for D. saccharalis. To ensure the long-term success of Bt maize for managing stalk borers in the mid-southern region, since 2004, a cost-effective Bt resistance monitoring program has been implemented in the region (Huang et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…The pots were kept on tables in the greenhouse allowing an approximately 1-m distance between plot to plot and 20-cm distance between pot to pot. Seed planting and plant management procedures in the greenhouse were similar to those described in Wu et al (2007). Fertilization, topping-up, and irrigation among other management practices were used when needed to ensure optimum growth.…”
Section: Corn Hybridsmentioning
confidence: 99%
“…Cry1Ab corn) that was commonly planted in the mid-southern region did not express a high dose against D. saccharalis as desired for the "high dose/structured refuge" IRM strategy (Wu et al, 2007). Recently, Ghimire et al (2011) evaluated six other Bt corn hybrids including four Cry1Ab (YieldGard® Corn Borer) and two Cry1F (Herculex I®) corn hybrids against Cry1Ab-susceptible, -resistant, and -heterozygous genotypes of D. saccharalis.…”
Section: Introductionmentioning
confidence: 99%